Mobile technology and the value chain: Participants, activities and value creation - Constantinos Coursaris; Khaled Hassanein; Milena Head (International Journal of Business Science & Applied Management (IJBSAM), 2008)
Technology has evolved significantly and it is increasingly being used by businesses and consumers alike. Technologies such as those supporting electronic business (e-Business) and mobile business (m-Business) are being used across organizations extensively in an attempt to improve operations and subsequently translate in either financial gains or strategic advantages. Opportunities for realizing either of the two types of benefits can be identified through an examination of a business' value chain. This conceptual study begins by proposing a business-centric interaction model that helps explain the interactions among all participants involved in an organization's possible activities. The paper then explores the potential fit of wireless and mobile technologies across a company's value chain through the citation of potential mobile and wireless business applications currently available. Finally, a discussion on the expected benefits and relevant concerns of mobile technology, as well as considerations for future research are provided.
Keywords: 650; mobile technology; value chain; mobile applications; m-Business; concerns